Preservation and recycling of heritage buildings in Malacca - Wan Ismail, Wan Hashimah (2013)
This paper elaborates on the preservation and recycling of the buildings along Tun Tan Cheng Lock Street, one of the important heritage streets in Malacca, Malaysia. The street was part of the historic city that was inscribed as World Heritage Site in 2008. Scholars stress that the practice of using the old buildings can save them from being replaced by new buildings. This practice also helps to preserve the identity of a place. The research involved site observation, literature review and interview. The findings indicate that there were both positive and negative interventions on the heritage buildings along the street.